Producción de neutrones en jets de microcuásares: inyección de partículas relativistas en el medio circundante - Escobar, Gastón Javier (2020)
The composition and launching mechanism of astrophysical jets are open problems in the relativistic astrophysics area, though not at all independent as comes up from the proposed launching models. To study the jet composition we introduce the relativistic neutron component, produced in the jet through hadronic interactions. These neutrons escape from the system and inject secondary relativistic particles in the nearby medium through their decay. Although these particles may account as an observable counterpart of the system as consequence of interactions with matter, radiation and magnetic fields in the medium, the main considered mechanisms produce very low luminosities. Therefore, these secondary particles may escape from the system as cosmic rays, carrying with them a fraction of the neutron population energy.